Pembuatan Chicken Sticks Dengan Pemanfaatan Tepung Daun Kelor Dan Pengaruhnya Terhadap Nilai Gizi Produk - Eduard kalendi wawu; Ina, Yessy Tamu; Pari, Aris Umbu Hina (JURNAL PETERNAKAN SABANA, 2025)
This research aims to determine the effect of adding moringa flour by analyzing the flavor and nutritional value of chicken sticks products. The research material used was 1 kg of fresh broiler chicken meat taken from the breast and thighs. This research used a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications, namely: P0= (control without adding Moringa flour; P1= Adding 5% Moringa leaf flour; P2= Adding 10% Moringa leaf flour; P3= Adding flour Moringa leaves 15%, so there were 20 sample units. The variables observed were water content, pH, organoleptic (color, taste, texture and preference), and total proximate profile test. The data obtained was then analyzed by variance at a level of 5%, the results were influential followed by the least significant difference test (BTN), the organoleptic data was processed statistically using the non-parametric Kruskall Wallis method. The results of the research showed that the use of Moringa flour at a concentration of 10% had an effect on increasing the panelists' acceptance of the Flavor and Nutritional Value elements of the product which included the Total Profile. Proximate.